2004
DOI: 10.1073/pnas.0304752101
|View full text |Cite
|
Sign up to set email alerts
|

Persistently active cannabinoid receptors mute a subpopulation of hippocampal interneurons

Abstract: Cortical information processing requires an orchestrated interaction between a large number of pyramidal cells and albeit fewer, but highly diverse GABAergic interneurons (INs). The diversity of INs is thought to reflect functional and structural specializations evolved to control distinct network operations. Consequently, specific cortical functions may be selectively modified by altering the input-output relationship of unique IN populations. Here, we report that persistently active cannabinoid receptors, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
137
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(146 citation statements)
references
References 38 publications
7
137
0
Order By: Relevance
“…In contrast, IvyCs and RSBCs were less likely to be functionally connected to simultaneously recorded MFs (n ϭ 5 monosynaptic pairs of 30 MF-IvyC pairs, 16.7%; n ϭ 3 monosynaptic pairs of 29 MF-RSBC pairs, 10.3%). The most striking difference in this regard was exhibited by the MFAs (Vida and Frotscher, 2000;Losonczy et al, 2004) that were never observed to receive monosynaptic EPSCs from MFs (n ϭ 0 connection of 30 MF-MFA pairs). Statistical analyses (Pearson's 2 test) of the probability of connections between identified CA3 GABAergic cells and nearby MF terminals indicated significant differences among the cell types ( 2 ϭ 16.8; p ϭ 0.0021).…”
Section: Target Selectivitymentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast, IvyCs and RSBCs were less likely to be functionally connected to simultaneously recorded MFs (n ϭ 5 monosynaptic pairs of 30 MF-IvyC pairs, 16.7%; n ϭ 3 monosynaptic pairs of 29 MF-RSBC pairs, 10.3%). The most striking difference in this regard was exhibited by the MFAs (Vida and Frotscher, 2000;Losonczy et al, 2004) that were never observed to receive monosynaptic EPSCs from MFs (n ϭ 0 connection of 30 MF-MFA pairs). Statistical analyses (Pearson's 2 test) of the probability of connections between identified CA3 GABAergic cells and nearby MF terminals indicated significant differences among the cell types ( 2 ϭ 16.8; p ϭ 0.0021).…”
Section: Target Selectivitymentioning
confidence: 94%
“…6). MFAs are found exclusively in the CA3 area and innervate specifically the stratum lucidum of CA3 (hence the name of the cell type) and the hilus (Vida and Frotscher, 2000;Losonczy et al, 2004) (note that it is the axons, and not the dendrites, that align with the MF termination zone). In agreement with previous studies, most of the axons of identified MFAs within the CA3 in our sample are located in the stratum lucidum, running parallel with the pyramidal cell layer (all MFAs had axons showing the latter property), and also send collaterals to the hilus (19 of 23 cells).…”
Section: Specific Description Of Cell Typesmentioning
confidence: 99%
“…CCK-expressing cells have been shown to be heterogeneous, including subpopulations with different morphology, electrophysiology, and expression of neuropeptides and calcium-binding proteins Cope et al, 2002;Kawaguchi and Kondo, 2002;Pawelzik et al, 2002;Losonczy et al, 2004). Thus, small CCKcontaining neocortical cells are usually positive for VIP and calretinin (Kawaguchi and Kondo, 2002) but lack CB 1 expression (Bodor et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to elucidate how MGL activity is regulated under physiological conditions. In the hippocampal CA3 area, persistently active CB1 receptors is reported to mute subpopulation of interneurons (Losonczy et al, 2004). It is possible that low MGL activities at presynaptic terminals may underlie persistent activation of CB1 receptors.…”
Section: Discussionmentioning
confidence: 99%